Organizational features legal regulation in the securities market - Гуренко-Вайцман, Марина Миколаївна; Мусін, Андрій Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In the article a question is affected to relation of jurisdiction and order of activity of administrative organs, whichprovide the administrative function of the securities. Also analised the state of the normatively legal adjusting of managementin a sphere of the securities.